Identification of Bacillus subtilis NRRL B-3275 as a Strain of Bacillus pumilus - Lovett, Paul S. (1969)
The physiological and biochemical properties of a species of Bacillus previously identified as B. subtilis NRRL B-3275 (B-3275) were compared with those of seven strains of B. pumilus and five strains of B. subtilis. The biotin requirement of B-3275, its inability to hydrolyze starch, and its failure to reduce nitrate indicate that the organism is more closely related to the B. pumilus strains than to those of B. subtilis. Hybridization of deoxyribonucleic acid (DNA) from B-3275 with that of the strains of B. pumilus showed a binding efficiency (compared with the homologous reaction) of 58 to 99%, depending on the strain. Hybridization with the DNA from any of the strains of B. subtilis did not exceed 24%. DNA from B-3275 was unable to transform two amino acid auxotrophic markers to prototrophy in a highly competent strain of B. subtilis 168. We conclude that B-3275 is a strain of B. pumilus which we designate as B. pumilus NRRL B-3275.